Pengaruh Pembelajaran Terpadu Terhadap Hasil Belajar Siswa di Sekolah Dasar - Anisa Zaenatun; Anisa Atha Setiani; Reza Farrah; Rosa Widyastuti; Ani Nur Aeni (Universitas Negeri Padang, 2021)
The purpose of the study was to prove the effect of using integrated learning in elementary schools on student learning outcomes in elementary schools in Sumedang Regency. This type of research is descriptive quantitative using a survey. The sample technique is total sampling, namely all teaching staff in SD Sumedang Regency. The technique of collecting with a questionnaire. Data analysis technique with simple descriptive analysis using the percentage formula. The results of the survey of 20 questions asked to the teacher showed that integrated learning had been going well, as evidenced by most of the 84% of the 50 participants who had implemented integrated learning. Student learning outcomes have been 80% of the 50 participants. The effect of integrated learning on student learning outcomes in elementary schools is 78% of 50 participants in integrated learning teaching aids play an important role as a tool to create an effective teaching and learning process.